The Implementation of Zoning System Policy in 10th State Senior High School of Surabaya - Tri Wahyuni; Erny Roesminingsih; Yatim Riyanto (Studies in Learning and Teaching, 2022)
This research aims to describe and analyze the implementation of zoning system policies at 10th State Senior High School Surabaya Methods of this research is using a qualitative approach with case study design and collecting data using interviews, observations and documentation. Data analysis techniques in this study use interactive models of analysis that have three components, namely data reduction, data presentation and conclusion. The results obtained from this study show that the implementation of the zoning system at the 10th State Senior High School of Surabaya is related to 6 variables, namely: (1) Size and the purpose of the zoning system policy in the implementation of New Student Admissions at 10th State Senior High School of Surabaya; (2) The resources formed by the AONL team at 10th State Senior High School of Surabaya; (3) The characteristics of the AONL Zoning System executors comitee; (4) The attitude of the registrants towards the implementation of zoning system policies in AONL at 10th State Senior High School of Surabaya is considered to be good enough; (5) The communication that occurs between implementers has been well established; (6) Economically, socially and politically prospective students in 10th State Senior High School of Surabaya are considered quite good.